Fracture Mechanisms In The As-Built And Stress-Relieved Laser Powder Bed Fusion Ti6Al4V ELI Alloy - Vilardell, A.M.; Fredriksson, G.; Yadroitsev, I.; Krakhmalev, P. (Optics and Laser Technology, 2018)
The influence of a stress-relief treatment on impact and fatigue properties of Ti6Al4V ELI samples manufactured by laser powder bed fusion was analyzed. The heat treatment resulted in removal of residual stresses, coarsening of needles and formation of precipitations between needles. In both, impact and fatigue tests, crack development was correlated to microstructural features. Fracture analysis was carried out by means of optical and electron microscopy to reveal the influence of microstructure on crack development. Ductile fracture was the dominating fracture mode at impact testing. Pore formation and coalescence were the main crack formation mechanisms. The microstructural changes led to a decrease in impact toughness after heat treatment. Presumably, this was a result of the precipitations between needles. Fatigue results showed multiple crack nucleation at the surface in both, as-built and stress-relieved material. The crack propagation rate was slightly higher and the crack was less deflected in the stress-relieved material due to the stress relief and coarsening of the microstructure.
Published Article
Keywords: Laser Powder Bed Fusion; Ti6A4V ELI; Impact And Fatigue Properties; Stress-Relief Treatment; Fracture Analysis